Increase in the Number of Firefighting Interventions and the Prevalence of Post-Earthquake Interventions in Zagreb and Banovina in 2020 - Pažin, Leo (Global journal of Business and Integral Security, 2024)
The research paper will describe firefighting as a multidisciplinary activity that includes the development of technical services within firefighting. Furthermore, the paper will describe and elaborate the continuous increase in the number of technical interventions in firefighting. In the Republic of Croatia, the need for technical interventions by firefighters is becoming more frequent. The entire technology, teaching and training of firefighters was based on knowledge from other countries. After the earthquakes in Zagreb and Banovina, firefighters in Croatia intend to receive additional training in order to be able to work in catastrophic situations. Firefighting personnel are being trained due to natural disasters in the Republic of Croatia. After the 2020 earthquake in Croatia, an increased number of interventions was recorded on a daily basis. Any type of training, procurement of equipment as well as education of the local population increases security in certain areas. Keywords: Firefighting, Natural disasters, Technical interventions, Earthquakes in Croatia.